Multicentre study of the main carbapenem resistance mechanisms in important members of the Enterobacteriaceae family in Iran. (May 2021) - Armin, S.; Fallah, F.; Karimi, A.; Azimi, T.; Kafil, H.S.; Zahedani, S.S.; Ghanaiee, R.M.; Azimi, L.
Abstract: Resistance to carbapenems has been increasingly reported from the Enterobacteriaceae family, with different mechanisms in different geographic parts of the world. This study investigated the mechanisms of carbapenem resistance in Escherichia coli, Klebsiella pneumoniae and Enterobacter spp. carried out as a multicentre study ( n  = 10). All third-generation cephalosporin-resistant E. coli, K. pneumoniae and Enterobacter spp. that had been recovered from the selected provinces were included. Modified Hodge test and Carba NP test were done as a phenotypical method for detection of carbapenemase; the most common carbapenemase was detected by PCR. We evaluated the presence of an active efflux pump by using cyanide 3-chlorophenylhydrazone. Overexpression of AcrA/B and presence of OqxAB was detected by real-time PCR and conventional PCR respectively. Microorganisms in this study included 58 E. coli, 95 K. pneumoniae and 60 Enterobacter spp. Modified Hodge test showed a sensitivity of 41% and a specificity of 83%, and the Carba NP test showed a sensitivity of 26% and a specificity of 92% for detection of carbapenemase. OXA-48 was the most frequently detected carbapenemase, followed by NDM-1. Thirty-nine percent and 27% of positive cyanide 3-chlorophenylhydrazone test organisms included active AcrA/B and OqxAB efflux pumps respectively. The result showed the Carba NP test was more specific than MHT. Data confirmed the involvement of AcrA/B and OqxAB efflux pump as a carbapenem resistance mechanism in selected bacteria. Similar to other reports from the Middle East, we found OXA-48 and NDM-1 to be the most frequent carbapenemase.